Industry Perceptions on the Need of Green Skills in Agribusiness Vocational Graduates - Mustika N Handayani; Ali, Mohamad; Mukhidin, Dinn Wahyudin (Journal of Technical Education and Training, 2020)
One of the global issue trends in vocational education is greening to support the achievement of sustainable development. Industry as one of the main stakeholders of vocational schools needs to know their views regarding the skills of prospective workers they need. This study aims to identify industry perceptions on the necessity of green skills in agribusiness vocational graduates. Five elements of green skills studied here are environmental awareness, innovation skills, communication skills, adaptability, and management of waste. A descriptive research design with quantitative approach was used in this research. Data was be gathered through a questionnaire involving fifty practitioners from various types of food industries. The result showed that the industry practitioners agreed that green skills is required by agribusiness vocational graduates. This finding can be used as a guide in integrating green skills into the agribusiness vocational curriculum by considering the skills most needed based on industry perceptions.